Decision-Making Strategies At The Simpang Raya Japura Restaurant - Agus Supriyadi; Meilya Karya Putri; Hasanah Yaspita (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze decision-making strategies at Rumah Makan Simpang Raya Japura. With increasing competition in the culinary industry, it is important for restaurants to develop effective decision-making strategies to improve performance and customer satisfaction. The research method used is a qualitative approach with interview and observation techniques. The results of the study indicate that Simpang Raya Japura Restaurant implements several strategies, including SWOT analysis, data-driven decision-making, and employee involvement in the decision-making process. Additionally, the study identifies challenges faced in implementing these strategies, such as fluctuations in customer preferences and price competition. These findings are expected to provide insights for restaurant managers in improving service quality and competitiveness in the market.